Influence of Demographic Factors on Job Satisfaction of Financial Institutions Workforce of Nepal - Shrestha, Indira (Journal of Business and Management, 2018)
This paper examines the influence of demographic factors on job satisfaction of employees of Nepalese Financial Institutions. The survey instrument was distributed to the employee of commercial banks, development banks and finance companies located at Lekhnath municipality and Pokhara Sub-metropolitan city. The sample size for this study was 150. The sample was selected using stratified sampling. This study presented communication, career development, and role of employee, working condition, recognition, and reward, immediate supervisor, and training pro-gram as factors of job satisfaction. Data were analyzed by using statistical tools like frequency, mean, and percentage. Moreover to test the hypothesis presented in this study, independent t-test, ANOVA analysis have been used. This research concluded that demographic variables (gender, job position, and age) influence the level of job satisfaction of employees of Nepalese financial institutions.